Obstacles to implementation of innovations in Brazil: how different companies perceive their importance - Kühl, Marcos Roberto (2013)
The objective of this study is to see how different companies perceive the importance of obstacles in the implementation of innovations. This is a descriptive research, developed through statistical analysis (factorial regression and ANOVA), based on secondary data, covering a sample of nearly 23,000 companies. The companies were organized into different groups. The results indicate a slightly higher perception on the part of small businesses, especially in the case of industrial companies. They also indicate that barriers related to economic issues are perceived to have greater importance than the others. It is concluded that different companies have different perceptions on most obstacles listed. Few differences were found between groups with respect to centralization of innovation activity in other units and many differences were found in the lack of qualified personnel. The lack of information about technology and the lack of qualified personnel have been identified as factors that contribute the most to whether or not companies innovate.